Aristotle’s Book Delta of the Metaphysics. ΠΕΡΙ ΤΩΝ ΠΟΣΑΧΩΣ ΛΕΓΟΜΕΝΩΝ Η ΚΑΤΑ ΠΡΟΣΘΕΣΙΝ On Terms Which Are Said in Many Ways or by Virtue of Addition - Wesoły, Marian Andrzej (Peitho. Examina Antiqua, 2016)
This paper offers a new Polish translation of Aristotle’s Book Delta of his Metaphysics. It takes into account its original title and subtitle that have been preserved in ancient catalogues. It is argued that the title and subtitle did not concerns any “ambiguity” of expressions as it is often mistakenly assumed, but rather the many ways of predicating (πολλαχῶς λέγεται) of various terms. Nor is it a typical lexicon of philosophical concepts, but rather a methodical survey of certain expressions that begin with physical and categorical specifications to make the terminological domain of the first philosophy more precise.